(untitled) (Shahroud Journal of Medical Sciences, 2017)
Background: Brucellosis is a zoonotic disease of humans and animals that has affected worldwide. Iran is one of the endemic areas infected with brucellosis. Early diagnosis of this disease may protect the affected children from disabilities and mortalities. This study aimed to evaluate the Brucella antibody levels in preschool children of the Shahroud city in Iran.Methods: This cross-sectional study evaluated 850 participants, in particular, school children from the Shahroud city. General information was collected by interviewing the children’s parents. Moreover, a 5 ml of blood sample was collected from all the children. The samples were studies using standard tube agglutination test (Wright) and 2-Mercaptoethanol. Thereafter, IgG and IgM levels were determined by the ELISA method.Results: A total of 850 children were enrolled, of which 51.2% were boys and 48.8% were girls, with a mean age of 5.17±1.55 years. Of the all children evaluated, 839 (97.5%) children had a titer <1/80 and 21 children (2.5%) had a titer ≥1/80. A significant difference was observed between the antibody titers in terms of gender (P=0.012), whereas no significant association was found among antibody titers with other variables such as age, history of nonpasteurized foods, exposure to animals, history of brucellosis disease, and parental occupation.Conclusions: The antibody titer for suspected brucellosis in preschool children of Shahroud was very low. According to the results of our study, in particular, in the endemic areas, a Wright’s titer of 1/80 in suspected cases for brucellosis can be considered as a diagnostic titer.